Does prescribing appropriateness reduce health expenditures? Main effects and unintended outcomes - Claudio Lucifora; Antonio Russo; Daria Vigani (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2021)
We evaluate the effectiveness of a reform to contain health-care costs by restraining general practitioners' (GP) ability to prescribe outpatient treatments, on the basis of strict appropriateness criteria. Using register data for a large Metropolitan area in Italy, we find a significant contraction in both outpatient expenditures (-24%) and volumes (-12%) after the reform. The effects on expenditures are found to be heterogeneous across GPs' characteristics, pointing out the mediating role of GPs' prescribing behavior. The reform also affected the composition of outpatient spending and produced unintended consequences on the demand for medical services of vulnerable groups, who were originally excluded from its application, as well as on access to emergency care.
Keywords: H51; I38; I18; 330; Prescribing appropriateness; Health-care expenditures; Primary care